OIL FROM THE PYROLYSIS OF RICE HUSK BIOMASS AND COFFEE GROUNDS MIXTURE WITH POLYPROPYLENE PLASTIC - Wulandari, Rani; Wijayanto, Danar Susilo; Saputra, Taufik Wisnu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This study aims to determine the effect of the ratio of the composition of the mixture of rice husk and coffee grounds with PP plastic on quantity (volume of pyrolysis oil and distillation results) and quality (yield, density, viscosity, visual and color), as well as to determine the ratio of biomass variation with plastic that produces the most oil and the best quality. This study was conducted by mixing rice husk and coffee grounds biomass with PP plastic in the form of RDF-3 with a variation in composition of 0% : 100%, 25% : 75%, 50% : 50%, 75% : 25%, and 100% : 0%. The pyrolysis results are in the form of oil which is then distilled to separate the compounds contained in it and produce clean oil, then the volume of pyrolysis oil and distillation results is measured, yield testing, density, viscosity, visual and color are tested. The test results showed that there was an effect of a mixture of rice husk and coffee grounds biomass with PP plastic on quantity (volume of pyrolysis oil and distillation results) and quality (yield, density, viscosity, visual and color). The volume of pyrolysis oil and distillation products was the highest ratio of 100% PP with pyrolysis oil of 616.67 ml and distilled oil of 178 ml. The results of the best yield test were obtained with a ratio of 100% PP of 82.39%. The best density test obtained a 100% PP ratio of 846.6 kg/m3, the results of this density lead to the specification of diesel fuel. The viscosity value of the best pyrolysis oil is obtained with a ratio of 100 % PP of 0.65499 cP which leads to the specification of gasoline type fuel. The best visual and color testing of pyrolysis oil was obtained with a ratio of 100% PP with a clear and bright visual appearance with a clear yellow color, which is in accordance with the specifications of diesel and gasoline fuel. It was concluded that the best configuration was obtained with a ratio of 100% PP which led to the specification of diesel fuel.